UPAYA MENINGKATKAN KEMAMPUAN PASSING BAWAH BOLA VOLI PADA - Irawan, Dedi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research uses research "Classroom Action Research" (Classroom Action Research) with variables: Improved Passing Down volleyball through media modified rubber ball. Subjects in this study were fifth grade students of State Elementary School 23 Palus Hulu subdistrict Belimbing Melawi totaling 28 students. This research technique using test and measurement, a test with a grating instrument measuring learning outcomes passing down the volleyball game. Analysis of data using percentages. These results indicate there is an increased ability under volleyball passing through modifications media inflatable balls At V grade students of State Elementary School 23 Palus Hulu subdistrict Belimbing Melawi. This is evidenced by the increased ability of passing down pretty good, that in the first cycle with an average value of 69.77 so the increase of 34.73%. while the average value on the second cycle is 82.14 so the increase of 58.62%. Keywords: Modified Rubber Ball, Passing Below